2010
DOI: 10.1177/030089161009600215
|View full text |Cite
|
Sign up to set email alerts
|

The Revised Piper Fatigue Scale (PFS-R) for Italian Cancer Patients: A Validation Study

Abstract: Despite the discussed limitations, PFS-R seems a valid and reliable multidimensional fatigue measure also adequate in Italian oncological settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
(50 reference statements)
3
18
0
Order By: Relevance
“…A previously performed factor analysis of the Swedish version [16] also indicated a possible division, reflected by the magnitudes of the factor loadings of the first two items compared with those of the latter three, even though the subscale held together. A single domain comprising Cognitive/Mood failed to be supported, corroborating earlier factor analytical studies both for the Swedish version [16] and for other international versions [10,13,14]. A bifactor solution with each of the three original domains treated as testlets, and with Cognitive/Mood treated as separate testlets (so making five in all), does support a dominant common factor, and with most of the nonerror variance being common, the summated raw score is, in practice, a sufficient statistic for estimating fatigue.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A previously performed factor analysis of the Swedish version [16] also indicated a possible division, reflected by the magnitudes of the factor loadings of the first two items compared with those of the latter three, even though the subscale held together. A single domain comprising Cognitive/Mood failed to be supported, corroborating earlier factor analytical studies both for the Swedish version [16] and for other international versions [10,13,14]. A bifactor solution with each of the three original domains treated as testlets, and with Cognitive/Mood treated as separate testlets (so making five in all), does support a dominant common factor, and with most of the nonerror variance being common, the summated raw score is, in practice, a sufficient statistic for estimating fatigue.…”
Section: Discussionsupporting
confidence: 82%
“…Subscales and total score range from 0 to 10 in the original version, with higher values indicating more intense fatigue. To date, the RPFS has been translated into Chinese [8] and Greek [9] and validated for use in France [10], The Netherlands [11], Brazil [12], and Italy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Three psychometric studies of non-English translations of the PFS-R, Greek [9], French [10] and Italian [34], also identified the same 4 subscales. In contrast, two studies found evidence for a 3-factor solution combining the domains of sensory with cognition/mood.…”
Section: Discussionmentioning
confidence: 88%
“…For example, an Italian study of cancer patients included relaxed/tense in the affective meaning subscale rather than the sensory subscale [32]. The Dutch version of the revised PFS for breast and lung cancer patients reported that all items were matched with the items of the original subscales [33].…”
Section: Discussionmentioning
confidence: 99%